GENRE-BASED APPROACH AND PRE SERVICE TEACHERS IN ELT: A PERSPECTIVE - Amalia, Lulu Laela (Jurnal Bahasa Lingua Scientia, 2014)
This paper aims to portray the implementation of Genre based Approach (henceforth GBA) in English Language Teaching context in Indonesia. The emphasize of the paper is on GBA as a new concept when it is first introduced as a new curriculum  in Indonesian education system and how it gives impact to Indonesian curriculum development. GBA, which is highly influenced by Halliday?s Systemic Functional Linguistics highlights the process of learning as opposed to the result of learning. Thus, the description on GBA implementation is expected to give different perspective in ELT in Indonesia.